2017
DOI: 10.1080/13554794.2017.1361452
|View full text |Cite
|
Sign up to set email alerts
|

What role for prism adaptation in the rehabilitation of pure neglect dyslexia?

Abstract: Prism adaptation (PA) has been successfully applied in the rehabilitation of spatial neglect, with significant transfer to classic neglect tests and activities of daily living. However, well-controlled studies were unable to replicate these findings, and recent reports suggest that PA may affect selectively visuo-motor symptoms. Here, a patient with pure left neglect dyslexia was tested before, immediately after, and 24 h after PA. Despite a significant adaptation aftereffect adaptation had no effect omissions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…In the VR environment, longer lines required eye-movements to be perceived entirely, which may have interfered with or even canceled the adaptation effects by recalibrating the coordinates of the sensory-motor reference frame. We also found no transfer effects in the landmark task, which is in good agreement with previous reports suggesting that PA may affect visuomotor performance more than purely perceptual measure ( Harvey et al, 1995 ; Gammeri et al, 2020 ; but see Ptak, 2017 ; McIntosh et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…In the VR environment, longer lines required eye-movements to be perceived entirely, which may have interfered with or even canceled the adaptation effects by recalibrating the coordinates of the sensory-motor reference frame. We also found no transfer effects in the landmark task, which is in good agreement with previous reports suggesting that PA may affect visuomotor performance more than purely perceptual measure ( Harvey et al, 1995 ; Gammeri et al, 2020 ; but see Ptak, 2017 ; McIntosh et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, at closer look several factors emerge that may systematically contribute to thè outcome of PA rehabilitation. First, PA may affect visuomotor performance more than purely perceptual measures (Ptak, 2017;Striemer & Danckert, 201 Ob). For example, PA was found to improve performance in thè classic line bisection task, but not in thè landmark task (Harvey, Milner, & Roberts, 1995), which requires judging thè accuracy of line pre-bisections (Striemer & Danckert,201 Oa).…”
Section: Introductionmentioning
confidence: 99%
“…Significant improvement of neglect signs has been observed after a single application of PA for a few minutes (3-5 min), while PA repeated for two weeks led to long-term effects lasting up to 6 months [48][49][50][51]. However, neglect does not improve in all treated patients, and clinical studies including several RCTs failed to provide evidence for lasting effects of PA on its clinical manifestations [48,[52][53][54][55][56]. In a meta-analysis of eight RCTs [52-54,57-59], Li et al [60] found five reports showing that patients treated with PA showed significantly better scores in a neglect battery [61] than the control group [49,53,58,59,62].…”
Section: Effects Of Prism Adaptation On Spatial Neglectmentioning
confidence: 99%